2016
DOI: 10.1177/1473225415606815
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s harder to go to court yourself because you don’t really know what to expect’: Reducing the negative effects of court exposure on young people – Findings from an Evaluation in Scotland

Abstract: In Scotland, the Whole System Approach to preventing and reducing offending includes the provision of court support for young people under 18 years. This article outlines the insights from an evaluation of one Scottish local authority's support service. Semi-structured interviews conducted with 26 participants were combined with observation of interactions between support workers and young people, with some additional follow-up statistical analysis of key outcomes. The insights suggest that the court support h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The articles forming part of the final eight included three which focused on parents’ experiences (Pennington, 2015, 2017; Richardson et al, 2014) and five in relation to children’s and young people’s voices (Block et al, 2010; Deuchar and Sapouna, 2016; Hobbs et al, 2014; Morash et al, 2014; Timms and Thoburn, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The articles forming part of the final eight included three which focused on parents’ experiences (Pennington, 2015, 2017; Richardson et al, 2014) and five in relation to children’s and young people’s voices (Block et al, 2010; Deuchar and Sapouna, 2016; Hobbs et al, 2014; Morash et al, 2014; Timms and Thoburn, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Deuchar and Sapouna (2016) interviewed 26 young people under 18 years of age attending court in Scotland. They reported that the young people found court support social workers (Whole System Team (WST) workers) helpful in explaining court processes and legal terminology, enabling them to be aware of their rights, improving their ability to participate and assisting many to avoid custodial sentences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has not been the case. Scotland's 'welfarist' approach to youth criminal justice (Deuchar and Sapouna 2016) has resulted in Glasgow's comparative neglect by the criminologists. Recent research focused upon territoriality, masculinity, and street socialization with some even arguing against the existence of youth gangs in Glasgow (Fraser 2013;Lawson 2013;Miller 2015).…”
Section: Gang Dynamicsmentioning
confidence: 99%